Peningkatan Performa 4 Stroke SI Engine menggunakan Voltage Stabilizer untuk Kontrol AFR - George Endri Kusuma; Sryang Tera Sarena; Mardi Santoso; Emie Santoso; Ekky Nur Budianto; Himawan Candra Buana (POLITEKNIK NEGERI BENGKALIS, 2021)
The manufacturer's rules apply Euro 3 and Euro 4 as an effort to reduce emissions in the air. The standard input voltage for the Engine Control Unit (ECU) is 12V to produce an ideal Air to Fuel Ratio (AFR) at a value of 14.7. However, in machine operation in the field, the voltage supplied by the battery cannot be constant at that number and causes the AFR to change too, especially in open-loop ECU systems. The input voltage that is too low can affect the AFR to be too high. The condition might cause the engine temperature to be too high and decreases engine performance. As a solution to this problem, this research develops a voltage stabilization mechanism (VC) to facilitate the setting of air and fuel for the engine to be constant at the desired value. To get the best AFR value, engine performance is tested with dyno tests including power, torque, fuel oil consumption, and AFR. The test results show that the best engine performance value reaches 16.7 HP at 10000 RPM and 13.35 Nm of torque at 8000 RPM, and a voltage of 12.5 V and AFR 14.11. The AFR value is used as input to the VC system, and the equipment can adjust the voltage automatically to stabilize the AFR at a predetermined value.